Solid-phase synthesis of oligouridine boranophosphates using the H-boranophosphonate method with 2′-O-(2-cyanoethoxymethyl) protection. (21st December 2021) - Matsuda, Hiromasa; Ito, Hiroaki; Nukaga, Yohei; Uehara, Sho; Sato, Kazuki; Hara, Rintaro Iwata; Wada, Takeshi
Graphical abstract: Abstract: Oligonucleotides with the boranophosphate (PB) modification attract much attention as promising therapeutic agents. The PB modification is useful for the development of small interfering RNAs (siRNAs); however, the chemical synthesis of long PB-oligoribonucleotides has not been achieved to date. This study reports the solid-phase synthesis of oligouridine boranophosphates using the H -boranophosphonate monomer with a 2′- O -(2-cyanoethoxymethyl) (CEM) protecting group. As a result of various investigations, the conditions for the solid-phase synthesis and removal of 2′- O -CEM groups were optimized. Notably, we found that the counter cation of a boranophosphate moiety plays an important role in the deprotection step of 2′- O -CEM groups. Finally, oligouridine boranophosphates were successfully obtained up to a dodecamer.